The Effect of Taxpayer Compliance, Use of E-Filing, Tax Audit, and Tax Avoidance on Tax Revenue at Tax Service, Extension, and Consultation Office (KP2KP) Sengkang Wajo District - Tenriwaru Tenriwaru; Zahara Saputri; Darwis Lannai (AJAR, 2024)
This study aims to determine the effect of taxpayer compliance, use of e-filing, tax audit, and tax avoidance on tax revenues. The research hypothesis uses a theoretical/concept basis supported by previous studies with the same variables. This research was conducted at the Tax Service, Counseling, and Consultation Office (KP2KP) Sengkang, Wajo Regency. This research is descriptive quantitative research, which uses primary data. The sample of this research is Tax Service, Counseling, and Consultation Office Taxpayers (KP2KP) of Sengkang, Wajo Regency, totaling 100 people. The hypothesis test used was multiple linear regression analysis with the help of SPSS version 25 software.The study results found that E-filing Taxpayer Compliance, and Tax audit, had a positive and significant effect on tax revenues at Sengkang's tax service, counseling, and consulting office (KP2KP), Wajo Regency. Meanwhile, tax avoidance has a negative and significant effect on tax revenues at the tax service, counseling, and consulting office (KP2KP) Sengkang, Wajo Regency.